2021
DOI: 10.1007/s42977-020-00062-0
|View full text |Cite
|
Sign up to set email alerts
|

Membrane nanotubes are ancient machinery for cell-to-cell communication and transport. Their interference with the immune system

Abstract: Nanotubular connections between mammalian cell types came into the focus only two decades ago, when “live cell super-resolution imaging” was introduced. Observations of these long-time overlooked structures led to understanding mechanisms of their growth/withdrawal and exploring some key genetic and signaling factors behind their formation. Unbelievable level of multiple supportive collaboration between tumor cells undergoing cytotoxic chemotherapy, cross-feeding” between independent bacterial strains or “cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 114 publications
(156 reference statements)
0
17
0
Order By: Relevance
“…Recently, another extra-cellular tube-like structure involved in bacterial communication in biofilms has been reported [ 15 ]. These structures are known as nanotubes, involved in bacterial communication and exchange of the DNA, protein and nutrients [ 15 , 16 ]. Recent research has suggested that nanotube-like structures were produced by multiple bacterial species attached to a solid surface or in biofilm communities [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, another extra-cellular tube-like structure involved in bacterial communication in biofilms has been reported [ 15 ]. These structures are known as nanotubes, involved in bacterial communication and exchange of the DNA, protein and nutrients [ 15 , 16 ]. Recent research has suggested that nanotube-like structures were produced by multiple bacterial species attached to a solid surface or in biofilm communities [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…To use this route, however, the levels of ROS transported cannot be too high, as the transmitting or receiving cells could be damaged. Cells living within a biofilm, colony, and/or within different plant and animal tissues, are thought to use juxtacrine signalling to mediate cell-to-cell ROS and redox signaling 10,11 . Moreover, it was suggested that ROS can enhance the size of tunneling nanotubes or PDs and facilitate juxtacrine signalling 23,57 .…”
Section: Discussionmentioning
confidence: 99%
“…Cell-tocell communication can occur between cells of the same species or organism (e.g., in a multicellular organism) 5,6 , as well as between cells of different organisms (e.g., during interactions of cells with different bacterial or fungal pathogens) 7,8 . Two of the most conserved cell-to-cell signaling pathways are paracrine, secretion of signals that are perceived by neighboring cells, and juxtacrine, communication between cells connected via tunneling nano tubes, gap junctions, or plasmodesmata [9][10][11] . Examples of these signaling pathways can be found in archaea, bacteria, unicellular eukaryotes, and multicellular organisms 12 .…”
Section: Introductionmentioning
confidence: 99%
“…It also remains to be seen whether yeast-yeast and/or yeast-hypha connections involve the protrusion of microtubules/actin filaments as it appears. Bacteria and higher eukaryotic cells, both, are able to connect through intercellular membrane tunneling nanotubes (TNT; Onfelt et al, 2006 ; Pande et al, 2015 ; Matkó and Tóth, 2021 ). Bacteria and archaebacteria form a network of these filaments which allow a whole community of cells to cross-feed ( Pande et al, 2015 ) and share signaling molecules and other compounds ( Bassler and Losick, 2006 ; Pande et al, 2015 ) or even vesicles ( Onfelt et al, 2006 ; Delage and Zurzolo, 2013 ).…”
Section: Discussionmentioning
confidence: 99%